(untitled) (Vietnam Journal of Community Medicine, 2024)
In 2022, pregnant women infected with COVID-19 were still a special concern for physicians at the National Hospital of Obstetrics and Gynecology. Objective: To evaluate the treatment of pregnant women with mild and moderate COVID-19 at the National Hospital of Obstetrics and Gynecology from January 2022 to December 2022. Methodology: This is a cross-sectional study among pregnant women hospitalized with moderate and mild COVID-19 diagnoses. Results: The rate of pregnant women with mild COVID-19 was 58.2%, moderate was 41.8%. The age group 25-29 had the highest incidence of COVID-19 in both study groups. The mean age in the mild COVID-19 group was 30.4±4.9 years and in the moderate COVID-19 group was 30.8±5.4 years. The average gestational age in the mild group at admission was 39.0±0.9 weeks and the moderate group was 39.0±1.0 weeks. The cesarean section rate in the mild COVID-19 group was 58.9% and in the moderate COVID-19 group was 41.1%. Conclusion: The incidence of mild and moderate COVID-19 at the National Hospital of Obstetrics and Gynecology is comparable. For pregnant women with mild and moderate cases of COVID-19, the treatment method still prioritizes cesarean section.